1976
DOI: 10.1021/jm00228a013
|View full text |Cite
|
Sign up to set email alerts
|

10-Hydroxy-4-methyl-2,3,4,5,6,7-hexahydro-1,6-methano-1H-4-benzazonine derivatives (homobenzomorphans) as analgesics

Abstract: Six 10-hydroxy-4-methyl-2,3,4,5,6,7-hexahydro-1,6-methano-1H-4-benzazonine derivatives 17a-f have been synthesized as potential analgesics. The synthesis of these compounds involved conversion of 4-(2-dimethylaminoethyl)-6-methoxy alpha tetralone derivatives 12a-f to their N-methyl analogues and the subsequent intramolecular mannich reaction with formaldehyde to give the 7-keto C-ring homobenzomorphans 14a-f from which 17a-f, respectively, were obtained. Compounds 17a-f are as potent as morphine as analgesics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…For the wide variety of modified benzomorphanes synthesized (2), all compounds were shown to be active (2, 3) at various levels, regardless of the nitrogen atom position and hence lone pair orientation. Although a "black or white" answer was not observed, minor structural variations in benzomorphan opiates have been associated with drastic changes in the relative agonist or antagonist properties (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the wide variety of modified benzomorphanes synthesized (2), all compounds were shown to be active (2, 3) at various levels, regardless of the nitrogen atom position and hence lone pair orientation. Although a "black or white" answer was not observed, minor structural variations in benzomorphan opiates have been associated with drastic changes in the relative agonist or antagonist properties (14).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been found to be very active as opioids: analgesic activity of title compounds were determined using optically resolved stereoisomers (2,3). Surprisingly, it was reported that the optical resolution gave no effect on the analgesic activity of compound I.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed we found that the rigid tyramine constraint described above redirects the polypeptide backbones away from the PEO contour analogous to Class I superposition with the added effect that the Phe 4 aromatic ring fell outside of the vector map for the C21 ring of PEO. A tyramine conformation different from rigid alkaloids is also justified on other grounds: for example: (1) the synthetic hybrids of enkephalinamide and metazocine, sharing in common the tyramine moiety, have been shown to be inactive [50], and (2) the nitrogen locus, which is variable in analgesics [51][52][53], could also be different in these opioid peptides and, by extension, would not manifest parallel structure-activity relationships as rigid alkaloids [54]. Indeed the model proposed by Portoghese et al [53] reconciles some of these apparent anomalies.…”
Section: Comparison With Other Receptor Modelsmentioning
confidence: 99%
“…The racemate and isomer were prepared as described in the literature (23)(24)(25). The method of preparation and optical rotation and melting points of the enantiomers leave no doubt about their optical purity.…”
Section: Drugsmentioning
confidence: 99%